2022
DOI: 10.3390/ijms23137257
|View full text |Cite
|
Sign up to set email alerts
|

Methuosis Contributes to Jaspine-B-Induced Cell Death

Abstract: Methuosis is a type of programmed cell death in which the cytoplasm is occupied by fluid-filled vacuoles that originate from macropinosomes (cytoplasmic vacuolation). A few molecules have been reported to behave as methuosis inducers in cancer cell lines. Jaspine B (JB) is a natural anhydrous sphingolipid (SL) derivative reported to induce cytoplasmic vacuolation and cytotoxicity in several cancer cell lines. Here, we have investigated the mechanism and signalling pathways involved in the cytotoxicity induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Further studies using VE-821, PIKfyve inhibitors, SB202190 and SB220025 could reveal novel mechanisms and targets responsible for this interesting phenotype relevant to anti-cancer therapy. Methuosis, another micropinocytosis mediated vacuolation process also shows RAB7+ vacuoles and crosstalk with autophagy/lysosomal transport pathways (23, 69). Micropinocytosis inhibitors (70) like dynasore and dyngo-4a does not inhibit SB202190-induced vacuolation in A549 cells (Figure 4A & Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies using VE-821, PIKfyve inhibitors, SB202190 and SB220025 could reveal novel mechanisms and targets responsible for this interesting phenotype relevant to anti-cancer therapy. Methuosis, another micropinocytosis mediated vacuolation process also shows RAB7+ vacuoles and crosstalk with autophagy/lysosomal transport pathways (23, 69). Micropinocytosis inhibitors (70) like dynasore and dyngo-4a does not inhibit SB202190-induced vacuolation in A549 cells (Figure 4A & Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Paraptosis, a caspase-independent cell death pathway with accumulation of cytoplasmic vacuoles originating from endoplasmic reticulum and swollen mitochondria has been targeted for cancer therapy (20, 21). Methuosis is another vacuolation dependent mode of programmed cell death where vacuoles originate from macropinosomes and swollen endosomes (22, 23). SB202190 was originally shown to induce vacuoles specifically in colorectal cancer cells (24, 25).…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism or pathway of methuosis or methuosis-like cell death remains unclear, but the involvement of Ras (Bhanot et al, 2010), Rac1 (Bhanot et al, 2010;Chi et al, 1999), Akt-mTOR (Liu et al, 2021), and AMPK (Bielsa et al, 2022) in a caspaseindependent manner has been reported. Consistent with these reports, nutlin-3a downregulated KRAS activity as well as the KRAS downstream signal, KRAS-PI3K/Akt-mTOR, but not MEK/ERK.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the vacuoles of normal HEK293T cells caused by the stimulation of jaspine B would gradually disappear as time went on (after 24 h), indicating that its induced methuosis has a certain selectivity toward the tested tumor cells. In a recent report by Bielsa et al , 35 they further proved that the cavitation induced by jaspine B was related to the activation of adenosine 5′-monophosphate activated protein kinase.…”
Section: Small Molecule Methuosis Inducersmentioning
confidence: 91%